The Financial Market Impact of UK Quantitative Easing - Francis Breedon; Jagjit S. Chadha; Alex Waters (University of Kent, School of Economics, 2012)
After outlining some of the monetary developments associated with Quantitative Easing (QE), we measure the impact of the UK's initial 2009-10 QE Programme on bonds and other assets. First, we use a macro-finance yield curve both to create a counterfactual path for bond yields and to estimate the impact of QE directly. Second, we analyse the impact of individual QE operations on a range of asset prices. We find that QE significantly lowered government bond yields through the portfolio balance channel by around 50 or so basis points. We also uncover significant effects of individual operations but limited pass through to other assets.
Keywords: E43; E44; E47; E58; 330; Term Structure of Interest Rates; Monetary Policy; Quantitative Easing